Modelling of Basic Yellow 28 adsorption onto activated carbon: batch and continuous process - Kol, Zeliha Betul; Duranoglu, Dilek (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThis study aims to model and investigate Basic Yellow 28 (BY28) adsorption onto activated carbon in batch and continuous process. Design/methodology/approachBatch adsorption experiments were carried out at 25 degrees C with 50 mg/L BY28 solution at pH 6 with different amounts of activated carbon. Freundlich and Langmuir adsorption isotherm models were used to model batch data. Pseudo-first-order and pseudo-second-order kinetic models were applied with linear regression. The changes of the breakthrough curve with the column height, flow rate, column diameter and adsorbent amount were examined in fixed bed column at room temperature. BY28 adsorption data were modelled by using different adsorption column models (Adams & Bohart, Thomas, Yoon & Nelson, Clark and modified dose-response) with non-linear regression. FindingsFreundlich model and pseudo-second-order kinetic model expressed the experimental data with high compatibility. Modified dose-response model corresponded to the fixed bed column data very well. Originality/valueAdsorption of Basic Yellow 28 on activated carbon in a fixed bed column was studied for the first time. Continuous adsorption process was modelled with theoretical adsorption models using non-linear regression.
Keywords: Basic Yellow 28; Activated carbon; Adsorption isotherms; Fixed bed column; Modelling; FIXED-BED COLUMN; AQUEOUS-SOLUTION; REMOVAL; DYES; Chemistry; Engineering; Materials Science